2014
DOI: 10.1177/1053825914524363
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning and Its Impact on Students’ Attitudes Toward Youth With Disabilities

Abstract: This research uses contact theory to examine the impact of a service learning class on college students’ attitudes toward people with disabilities. Students were involved in both lecture material and working directly with people with disabilities in a therapeutic camp environment. Eighty-four students responded to the questionnaires at three time periods over the course of the semester. One-way repeated measures ANOVA and mixed-model ANOVA were performed to study the changes in students’ attitudes. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 41 publications
(57 reference statements)
1
12
0
2
Order By: Relevance
“…Finally, there was evidence of shifts in preservice educators' beliefs both in how students learn and their role as educators. Similar to the findings in Wozencroft, Pate, and Griffiths (2015), the pre-service educators perceived students with disabilities changed over the course of the se-mester throughout their experiential learning experiences. Although the review of assignments showed that progress was made in several areas, not surprisingly given that preservice special educators were early into their preparation program, there continued to be some challenges amongst them on how to meet all the individual literacy needs of their students with disabilities.…”
Section: Discussionsupporting
confidence: 69%
“…Finally, there was evidence of shifts in preservice educators' beliefs both in how students learn and their role as educators. Similar to the findings in Wozencroft, Pate, and Griffiths (2015), the pre-service educators perceived students with disabilities changed over the course of the se-mester throughout their experiential learning experiences. Although the review of assignments showed that progress was made in several areas, not surprisingly given that preservice special educators were early into their preparation program, there continued to be some challenges amongst them on how to meet all the individual literacy needs of their students with disabilities.…”
Section: Discussionsupporting
confidence: 69%
“…The findings of these studies confirm that S-L has positive effects on students, community partners and teaching staff (Daniels et al, 2015; Rutti et al, 2016). Improvements are found in teamwork (Largent, 2013; Wilkinson et al, 2013; Hildenbrand and Schultz, 2015; Young and Karme, 2015), cultural intelligence (Mosakowski et al, 2013), cognitive and metacognitive strategies (Mosakowski et al, 2013; Young and Karme, 2015), clarification of professional vocation (Wilkinson et al, 2013; Gezuraga and Malik, 2015), respect for diversity (Wilkinson et al, 2013; Tinkler et al, 2015; Wozencroft et al, 2015), empowerment (Winans-Solis, 2014) and political awareness (Blankson et al, 2015). S-L is also found to help students in tackling the challenges of the practicum (Coffey and Lavery, 2015) and developing empathy (Curtin et al, 2015; Young and Karme, 2015), communication skills (Curtin et al, 2015), academic development (Hébert and Hauf, 2015; Hildenbrand and Schultz, 2015; Wozencroft et al, 2015), social commitment (Hébert and Hauf, 2015; Hildenbrand and Schultz, 2015), interpersonal skills (Hébert and Hauf, 2015; Hildenbrand and Schultz, 2015), knowledge transference (Hildenbrand and Schultz, 2015), intercultural awareness (Hildenbrand and Schultz, 2015), reflection as a tool for connecting service with course contents (Largent, 2013; Wozencroft et al, 2015), resilience (Daniels et al, 2015) and the development of values (Young and Karme, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Kolb's ELT is attributed to the increase in scores, particularly because of the added value experiential learning contributes by providing students deeper understanding and richer experiences (Kolb, 1984). Experiential learning is credited with connecting linkages in the subject matter by allowing students to observe the vast associations that are present in the food and fiber industry (Wozencroft, Pate, & Griffiths, 2014).…”
Section: Conclusion 3: Experiential Learning Is a More Effective Methmentioning
confidence: 99%